Navigating Through the Maze: Practical Constraints in the Implementation of Forest Regulations (FLEGT) in Ghana - Sarfo-Adu, Gordon Kofi (Environmental Management and Sustainable Development, 2021)
The European Union Forest Law Enforcement on Governance and Trade (EU-FLEGT) Action Plan seeks to promote widespread sustainable forest management and relies largely on transnational actors and international law in its operationalization. The EU FLEGT sets out EU custom regulation through Voluntary Partnership Agreements (VPAs) which is a bilateral agreement between the EU and wood exporting countries with instruments aimed at promoting sustainable practices within the forest resources value chain. Ghana became a signatory to the FLEGT VPA since 2007, as part of the process, it is required to use technology to track timber logging from source to point of export. Issues of networks and inter-agency collaboration and dealing with human elements remain crucial in ensuring effective operationalization. Adopting a qualitative case study design as well as theories and concepts from the public policy implementation literature, this study examines the implementation vagaries of the FLEGT VPA in Ghana. Although the VPA is a laudable idea of using Information Technology (IT) in effectively tracking timber to its original source to ascertain legality or otherwise of the timber, the needed IT infrastructure and resources have not matched up with the goal. Additionally, the VPA implementation is expensive and has come with additional cost to the implementers, The study further observes that the increasing ‘red flags’ that are raised on the Ghana Wood Tracking System is a blend of technical errors emanating from negligence or capacity challenges and human manipulation. This calls for regular consultations and workshops with relevant stakeholders in order to assess which skills are deficient and a need to beef up through on-the-job training. The domestic market and trading activities tend to fuel demand for illegal timber hence a constraint to the full realization of the VPA objective. The study makes policy suggestions on how to address these implementation challenges.